The Metabolome of a Cyanobacterial Bloom Visualized by MS/MS-Based Molecular Networking Reveals New Neurotoxic Smenamide Analogs (C, D, and E) - Via, Christopher W.; Glukhov, Evgenia; Costa, Samuel; Zimba, Paul V.; Moeller, Peter D. R.; Gerwick, William H.; Bertin, Matthew J. (Frontiers in Chemistry, 2018)
Members of the cyanobacteria genus Trichodesmium are well known for their substantial impact on nitrogen influx in ocean ecosystems and the enormous surface blooms they form in tropical and subtropical locations. However, the secondary metabolite composition of these complex environmental bloom events is not well known, nor the possibility of the production of potent toxins that have been observed in other bloom-forming marine and freshwater cyanobacteria species. In the present work, we aimed to characterize the metabolome of a Trichodesmium bloom utilizing MS/MS-based molecular networking. Furthermore, we integrated cytotoxicity assays in order to identify and ultimately isolate potential cyanotoxins from the bloom. These efforts led to the isolation and identification of several members of the smenamide family, including three new smenamide analogs (1-3) as well as the previously reported smenothiazole A - hybrid polyketide-peptide compounds. Two of these new smenamides possessed cytotoxicity to neuro-2A cells (1 and 3) and their presence elicits further questions as to their potential ecological roles. HPLC profiling and molecular networking of chromatography fractions from the bloom revealed a complex secondary metabolome, generating hypotheses with respect to the environmental role of these metabolites and the consistency of this chemical composition across genera, space and time.